Specific capacity optimization of nickel cobalt phosphate using response surface methodology for enhanced electrochromic energy storage performance - Mustafa, Muhammad Norhaffis; Mohd Abdah, Muhammad Amirul Aizat; Numan, Arshid; Sulaiman, Yusran; Walvekar, Rashmi; Mohammad Khalid (Elsevier, 2023)
In this paper, we report the optimization of nickel cobalt phosphate (NiCoP) as a positive electrode material by response surface methodology and central composite design (RSM/CCD) for electrochromic energy storage applications. The NiCoP composite was prepared using the facile electrodeposition technique, where four input variables (concentration of precursors, number of CV cycles, and scan rate) were optimized simultaneously towards the surface response (specific capacity). The statistical analysis showed that all four factors have significantly affected the specific capacity of NiCoP. The reduced quadratic model obtained can accurately predict the specific capacity of NiCoP electrode material up to 97% with a 3% residual standard error. The novel NiCoP electrode materials display remarkable electrochromic properties (67.57 cm2/C) with reversible color changes from light green (0 V) to dark brown (0.5 V) and outstanding supercapacitive performance (323.74 C/g) owing to the synergistic effect of bimetallic oxides (NiCo) that help to produce more active sites, as well as increase the electrical conductivity and high surface area phosphate, which is advantageous to the transport of ions. Furthermore, the as-prepared NiCoP//Ac device shows a remarkably high specific energy of 10.88 Wh/kg at a specific power of 750 W/kg (1 A/g), and the NiCoP//Ac device is capable of retaining up to 70% of its capacity even after 5000 cycles, demonstrating good energy storage performances.